Peripheral Inflammation Results in Increased Excitability of Capsaicin-Insensitive Nociceptive DRG Neurons Mediated by Upregulation of ASICs and Voltage-Gated Ion Channels - Duzhyy, Dmytro E.; Voitenko, Nana V.; Belan, Pavel V. (Frontiers in Cellular Neuroscience, 2021)
Previously we have characterized capsaicin-insensitive low pH-sensitive (caps-lpH+) subtype of small-sized nociceptive DRG neurons, that express acid-sensing ion channels, T-type Ca2+ channels and have isolectin B4-negative phenotype. These neurons demonstrated increased excitability in a model of long-term diabetes, likely contributing to chronic pain sensation. Here we studied changes in excitability of the caps-lpH+ neurons and underlying changes in functional expression and gating properties of ion channels under CFA-induced peripheral inflammation. We have found that under these pathological conditions functional expression of ASICs and voltage-gated Na+ channels was increased. In addition, T-type Ca2+ current was significantly increased in the neurons at the membrane potentials close to its resting value. Altogether, the observed changes in channel functioning shifted a pH level evoking an action potential towards its physiological value and led to an increase of evoked and spontaneous excitability of the caps-lpH+ neurons that may contribute to hyperalgesia and chronic inflammatory pain.